Pengaruh locus of control, keahlian auditor, komitmen organisasi terhadap perilaku underreporting of audit time (studi empiris pada kap pekanbaru& padang) - Yolanda Safitri Nelaz; Kamaliah '; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study seeks to analyze the relationship between the factors that affect the auditor'sacceptance of under-reporting time. Auditor’s who worked in Public Accounting in Indonesia isan object in this study using questionnaire-based survey that was sent.The data have beencollected and analyzed using SPSS. Expectancy theory and the theory of goal setting is the basictheory used to explain the behavior of auditors underreporting time in accepting.The results ofthis study found that locus of control auditor’s expertise, organizational commitment variables have a effect on acceptance of under-reporting time.Keywords : locus of control, auditor’s expertise, organizational commitment, acceptance of under-reporting time